A numerical study of coupled estuary–shelf circulation around the Pearl River Estuary during summer: Responses to variable winds, tides and river discharge. (July 2015) - Zu, Tingting; Gan, Jianping
Abstract: The mean (sub-tidal) circulations in the Pearl River Estuary (PRE) and over the adjacent shelf are interactive. They are driven by multi-forcing of winds, tides, and the buoyancy of river discharge. Utilizing a validated three-dimensional, high resolution numerical model, we find that the circulation in the PRE during summer is dominated by an advective gravitational two-layer circulation in the upper estuary and the landward part of the lower PRE, where the surface flow pattern also varies with the upwelling winds. The circulation in the seaward part of the lower PRE is governed by both gravitational circulation and geostrophic intrusive current from the shelf. The pattern and intensity of these circulations are largely modulated by variable wind forcing. The cross-shore upwelling shelf circulation off the PRE enhances the water exchange rate between the shelf and the PRE, but the net intrusive transport into the PRE is negatively correlated with the intensity of upwelling-favorable wind stress. Relatively strong water exchange rate between the shelf and estuary occurs during upwelling, which reduces the flushing time of the estuary. Although the ebbing/flooding tide strengthens/weakens the eastward alongshore upwelling current, tidal effect on the upwelling circulation and on the net transport between the shelf and estuary is not significant over the sub-tidal period. The shelf influences the estuary mainly through the intrusions of the shelf waters at the western bank and along the two navigation channels of the PRE; and they are governed by geostrophic cross-shelf upwelling circulation and by gravitational intrusive currents due to pressure gradients, yielded by the alongshore variation of the upwelling shelf circulation and by the buoyancy forcing of the river plume, respectively.